Elaboración de una mezcla en polvo isotónica enriquecida con aminoácidos de cadena ramificada para preparar una bebida destinada a deportistas - Mejía Burgos, Gabriela Elizabeth (2023)
Hydration is one of the factors that most impact athletic performance, associated with the consumption of water, electrolytes, carbohydrates, and vitamins, among other substances. The industry has developed different product lines to satisfy this need. The present research aimed to formulate isotonic powder mixes enriched with branched-chain amino acids (BCAAs) to prepare a hydrating beverage for athletes. Several trials were conducted to obtain three formulations or treatments that underwent physicochemical and microbiological analyses to verify their quality and stability. The results of the analyzed parameters were subjected to analysis of variance (ANOVA) and Tukey's test (p<0.05) to determine statistical significance. Additionally, an acceptability test was carried out with 60 athletes. Based on the preference recognition of the treatments evaluated in this acceptability test, a rank-based analysis of variance (Friedman) was applied to determine their significance. Regarding the obtained results, the osmolarity values for T1 were 272 mOsmol/L, T2 was 313 mOsmol/L, and T3 was 275 mosmol/L, with contributions of minerals (sodium, potassium, and calcium), branched-chain amino acids (Lleucine, isoleucine, and L-valine), and sugars that help in the process of replenishing what the body uses during physical exercise. The preferred treatment was T2, which was selected after a statistical analysis that showed a significant difference in the preference of the panelists. The moisture parameters and microbiological research in the solid product remained with minimal variation during the 30 days after opening the jar. The physicochemical analysis results comply with the values established in the Colombian technical standard NTC 3837. Therefore, the company NUTRIÓN, the project sponsor, will adopt this formulation